Economic Valuation of Marine Tourism Dutungan Island by Travel Cost Method in Mallusetasi Subdistrict, Barru Regency, South Sulawesi Province - Mahmud, Medinah; Tahang, Hamzah; Hasani, M. Chasyim; Made, Sutinah; Fakhriyyah, Sitti (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
This study aims to determine the factors that influence the intensity of tourist visits to the Dutungan Island, Mallusetasi Sub-district, Barru Regency, South Sulawesi Province and The economic value of the Dutungan Island marine tourism object. This study uses quantitative descriptive and data collection techniques are observation and questionnaires. The population in this study are tourists with the purpose of traveling. The sampling technique used was accidental sampling with a total sample of 43 respondents. This research was conducted in April-May 2021 on Dutungan Island, Mallusetasi Sub-district, Barru Regency, South Sulawesi Province. The data analysis methods used were multiple linear regression analysis and travel cost analysis. The results of this study indicate that the factors that influence the intensity of tourist visits are travel costs, completeness of tourist attraction facilities, distance, accessibility, age and income. The economic value of the Dungan Island marine tourism object is IDR 1,188,895,920.